Clarification of the relationship between the members of the family Thermomonosporaceae on the basis of 16S rDNA, 16S-23S rDNA internal transcribed spacer and 23S rDNA sequences and chemotaxonomic analyses - Zhang, Z. (2014)
International Journal of Systematic and Evolutionary Microbiology